Eraser reborn - Weiss, Michael D.; Puryear, Tony 1957-; Green, Walon 1936- (Warner Bros. Entertainment Inc., 2022)
A U.S. Marshal 'erases' a federal witness faking her death to hide her deep in the witness protection program only to have a breach within his department that puts them both on the run
Wide screen
Originally released as a motion picture direct-to-video in 2022
Sequel to: Eraser (1996)
Special feature: The warrior and the witness: Making Erase, reborn
Keywords: United States marshals / Drama; Death / Drama; Witnesses / Protection / Drama; Assassins / Drama; Assassins; Death; Witnesses / Protection; Action and adventure films; Feature films; Video recordings for the hearing impaired; Fiction films; Drama; Motion pictures; Film; DVD-Video